Relasi Sosial antar Siswa dalam Keragaman Budaya di SD Negeri 01 Kajen Kabupaten Pekalongan - Rizky, Shafa Setya; Astuti, Tri (Universitas Nusantara PGRI Kediri, 2025)
Social relations are relationships between individuals, in this case students, with the aim of interacting with each other. This social relationship is carried out by students who have cultural diversity, the cultural diversity in question is religious and socio-economic. This study aims to analyze social relations between students in cultural diversity, the obstacles faced, and the efforts made in dealing with obstacles to social relations at State Elementary School 01 Kajen Pekalongan Regency. Data collection techniques were observation, interview, and documentation. This research used a qualitative approach of case study type. The research subjects were large classes, namely classes 4, 5, and 6. Data analysis techniques are data collection, data reduction, data display, and conclusion drawing. Based on the results of the study, it can be explained that social relations are established in two forms, namely accommodation and cooperation. The obstacles faced by students in cultural diversity are the lack of understanding and awareness of cultural differences. Efforts made in dealing with obstacles are both principals and teachers hold several policies. The conclusion is that social relations between students have been well established with few obstacles. Social relations can occur because of habituation in the form of tolerance.